The economics of going paperless: the case of container freight company - Bradwell, Rebecca S. (Kansas State University, 2009)
Over the last few years there have been many changes to the container export industry. There are a variety of reasons for these changes including exchange rate fluctuations, fuel and energy price fluctuations and their effects on bulk freight rates. The pressure to enhance and remain competitive has also increased amid these rapid changes. An effective strategy is for companies to focus attentions on costs they can control. In the container freight industry, one of these costs is reducing the “paper” aspects of operations and increasing its “electronic” aspects. This thesis focuses specifically on evaluating FileBound®, document management software, for the purpose of going “paperless” in a Container Freight, Non-Vessel Operating Common Carrier (NVOCC) and freight forwarding company. Going paperless has many advantages: increased efficiency, paper and printing cost savings, time savings, storage cost savings, environmental benefits, efficient file retrieval, and enhanced customer service. By adopting the FileBound® technology, the case study company hopes to achieve most of these benefits, allowing it to reduce overall costs, and especially, reduce the number of employees managing physical documents and move people into sales and marketing. The critical assumption of the study was that the electronic processes contributed to time savings and it is from these time savings that most of the other benefits emanated. Therefore, a time study was conducted to determine the time savings resulting from using FileBound® in comparison to the current method in the file completion process. The data collected was analyzed using regression analysis to determine the factors that influenced time savings, if any, and their statistical significance. There are three specific activities involved with the process of completing a transaction in the container freight business: booking, instruction and bill of lading. The analysis was conducted for each of these steps in the process. The results show that the different methods, FileBound® or manual, were not statistically significant on determining the time it took to complete the file. That being said, this thesis recommends that a mixture of both the FileBound® and manual method be used to take advantage of the potential cost savings.
Keywords: Container Freight; Paperless Office; Efficiency; Cost Savings; Time Experiments; Business Administration, Management (0454); Economics, Agricultural (0503); Transportation (0709)